Effect of Gamma Rays on Seed Germination, Seedling Survival and Morphology in Garden Balsam (Impatiens balsamina L.) - Chedeo ์Nusanisa; Wamaedeesa, Raheema (Princess of Naradhiwas University Journal, 2021)
This study aimed to investigate the effect of acute gamma irradiation on seed germination, seedling survival and morphology in garden balsam (Impatiens balsamina L.). The seeds were acute irradiated with gamma rays at the dose of 0, 50, 100, 200 and 300 gray. All the four gamma ray doses were found to decrease the seed germination rate and survival rate of seedlings of Impatiens balsamina L. Gamma radiation dose of 50 gray resulted in darker fuchsia petal color than dose of 0 gray. Some flower had blemish petal color after irradiation with 100 and 200 gray.